Red inalámbrica de banda ancha con seguridad perimetral en las áreas urbanas y rurales del cantón Tosagua - Santana Montesdeoca, Michael Jhonny (2016)
The main objective of the implementation of the wireless broadband network perimeter security in urban and rural areas of the canton Tosagua is providing free internet service to the beneficiaries places where people can have easy access to services that the global area network provides, avoiding expenses such as; cost of service or transport. To carry out this thesis waterfall methodology was used using a sequential order in each of the activities. This process started visiting the places where the beneficiaries live in order to determine the technical requirements for the deployment of the network, observation was made through some interviews to the Director of Technology Department of Tosagua GADM as well as the technological infrastructure that. Once the necessary information is compiled, the wireless network topology was designed, in addition Mobile Radio software was used to check the feasibility of the links and the strategic location of the equipment. He proceeded to the installation and configuration of wireless devices in established places, the firewall solution was also determined to provide perimeter security to the network, following the installation and configuration of pfSense distribution. After the installation of equipment and the implementation of the firewall, tests were conducted to confirm the proper functioning of the infrastructure which could demonstrate compliance with the objectives.